Development of a structured interview for the modified version of the Beth Israel Hospital psychosomatic questionnaire for alexithymia - Komaki, Gen; Baba, Takanobu; Yoshida, Toshiyuki; Arimura, Tatsuyuki; Moriguchi, Yoshiya; Maeda, Motonari (Frontiers in Psychiatry, 2024)
Previous findings and observations in studies of self-reported measurements such as the Toronto Alexithymia indicate that it is possible to be misled by their shortcomings, such as other psychological characteristics like neurosis and depression.Objective: To overcome the limitations of self-report questionnaires for alexithymia, we developed a structured interview for the modified version of the Beth Israel Questionnaire (m-SIBIQ) and confirmed its reliability and validity.The m-SIBIQ is a modified version of the BIQ composed of twelveitems. Scoring is on a 7-point Likert scale; higher points indicate that a person is more alexithymic. Ninety-two adolescents were interviewed and the reliability was examined by exploratory and confirmatory factor analyses. For the concurrent and convergent validities, correlation analysis was done between the scores of m-SIBIQ and the self-reported questionnaires; Toronto Alexithymia Scale (TAS-20), NEO Five-Factor Inventory (NEO-FFI), Emotional Empathy Scale (EES), Interpersonal Reactivity Index (IRI), Anxiety Scores, and Beck Depression Inventory-II (BDI-II).: Good reliability was obtained. Confirmatory Factor Analysis indicated two good models of two factors each; Model A, Affect Awareness (A.A.) and Operatory Thinking (O.T.) and Model B, Alexithymia (Alex) and Dreams. Stepwise multiple regression analysis done for each model were satisfactorily explained by the scores of Openness to experience of NEO-FFI and Fantasy of IRI. There were no correlations between the m-SIBIQ and BDI-II scores.The m-SIBIQ is a reliable and valid instrument for assessing the alexithymia of Japanese adolescents.